Exchangeable Al, peanut growth, and nodulation on Ultisol Bogor as affected by ameliorant proportion of lime and organic matter - Cahyani, Vita Ratri; Firmansyah, Mohammad Iqbal; Cahyono, Ongko; Widijanto, Hery (Brawijaya University, 2024)
Ultisols are characterized as acid soils with high exchangeable Al as the primary constraint for plant growth. This study aimed to investigate the effect of the proportion of lime and organic matter in decreasing exchangeable Al on Ultisol Bogor and continued to observe the impact on the growth and nodulation of peanuts. The pot experiment used a completely randomized design with a single treatment of the addition of ameliorant consisting of 12 levels of the treatment of lime (calcite and dolomite), organic matter (dry cow dung and rice straw compost), and their combinations with three replications. The first step was applying the ameliorant and incubating for eight weeks, then continuing the cultivation of peanuts. Results showed that during incubation, the decrease in exchangeable Al levels varied between treatments, along with an increase in soil pH and available P. The treatments of calcite 100% (T1) and dolomite 100% (T2) showed the highest increase in soil pH and available P and the highest decrease in exchangeable Al. The result of plant growth showed that the highest plant dry weight, N-uptake, and P-uptake were obtained by the treatment of dolomite 25% + rice straw compost 25% + dry cow dung 25% + NPK 25% (T10), whereas the highest number and total weight of nodules were obtained by the rice straw compost 50% + dry cow dung 50% (T7) and dolomite 25% + rice straw compost 75% (T8).